Bioecology of coral reef in Panjang Island of Central Java Indonesia - Suryono Suryono; Ambariyanto Ambariyanto; Munasik Munasik; Diah Permata Wijayanti; Raden Ario; Ibnu Pratikto; Nur Taufiq-Spj; Syahrial V. Canavaro; Tiara Anggita; Bayu Kreshna Adhitya Sumarto; Justin Cullen (Marine Science Department Diponegoro University, 2021)
Coral reefs currently are suffered from natural factors along with increasing anthropogenic activity. Panjang Island, a small reef island located in Jepara Regency, may also be experiencing such conditions. Therefore, this work was aimed to observe the condition of the coral cover of Panjang Island. Line intercept transect was applied to survey the coral cover and mortality index from fourteen stations. Insitu data consisted of the bottom substrate composition of the reefs and the physical parameters of the sea. The secondary data, i.e. coral reef area maps from 2001 to 2019 were taken from Landsat Image 7 and 8, data of wind were obtained from www.ogimet.com, while tidal data were collected from BMKG. The bathymetry was determined from the Geospatial Information Agency data, salinity global analysis forecast Phy 001.024 (CMEMS). Sea surface temperature (SST), and chlorophyll-a distribution were analyzed using ENVI software. The result showed that Panjang Island has a poor to the moderate condition of hard coral. Two out of six categories of abiotic and dead coral were found to be high. The mortality index of coral was in the high category (average 0.52). During research periods the sea waters were characterized by high sea surface temperature (29.34-30.94°C), chlorophyll-a was also tended to be high (0-2.65 mg.m-3), and an average of salinity was high 32 ‰. The weak currents came to all sides of the island, therefore the coral reef was not exposed to extreme currents. The waves came from the east, then the energy decreases after being blocked by coral reefs on the eastern side of the island, so that coral reefs in the northeast and south sides were safer to be exposed. The results suggest that hydrodynamic ecology directly or indirectly affected the percentage of coral cover and mortality index at the reefs of Panjang Island.